An Error Types Analysis on YouTube Indonesian-English Auto-Translation in Kok Bisa? Channel - Naftalia Laksana; Siegfrieda A. S. Mursita Putri (Universitas Sanata Dharma, 2018)
This study investigates the error types that commonly occur in the translation produced by YouTube auto-translate. This research uses error classifications from Vilar et al. (2006). The data were fourteen videos from Kok Bisa? channel. The source text and target text from YouTube auto-translate were aligned and analyzed in terms of the error types. This was a mixed quantitative and qualitative study and a primary research. The result shows that the most frequent error types are wrong lexical choice, bad word form, missing auxiliary word, short range word level word order and extra word. The other error types rarely occur in the translation.Keywords: translation error, error types, YouTube auto-translate